Pengawasan Penggunaan Tenaga Kerja Asing Di Sumatera Barat - Lerri Pattra (UIR Press, 2021)
The Republic of Indonesia was founded, the Indonesian people have realized that work is a human need for citizens. This is stated and mandated in Article 27 paragraph (2) of the 1945 Constitution which states that